Dimorphism of 1, 4-dibromo-2, 5-bis(bromomethyl)benzene: crystallographic and physico-chemical investigations. Issue 17 (14th April 2016) - Näther, Christian; Jess, Inke; Kuś, Piotr; Jones, Peter G.
Abstract : The compound 1, 4-dibromo-2, 5-bis(bromomethyl)benzene is dimorphic; formI (triclinic, left) is metastable, formII (monoclinic, right) stable at room temperature. Abstract : Two polymorphic modifications of 1, 4-dibromo-2, 5-bis(bromomethyl)benzene have been discovered and structurally characterized; their thermodynamic relationships and transformation behaviour have been investigated. FormI crystallizes in the triclinic space group P 1̄, whereas formII crystallizes monoclinic in space group P 21 / c, both with imposed inversion symmetry of the molecule. Their crystal structures involve layers, in which the molecules are linked by intermolecular Br⋯Br interactions to form similar systems of linked rings. Initial studies involved batches consisting of pure formI or a mixture ofI with traces ofII (as obtained by chance from the synthesis), but solvent-mediated conversion experiments in various solvents clearly prove that formII is the thermodynamically stable form at room temperature. Thermomicroscopic and heating-rate-dependent DSC measurements show that the melting point of formI is slightly higher than that of formII and that the higher melting polymorph exhibits the lower heat of fusion. Therefore, formI becomes thermodynamically stable at higher temperatures and both forms are related by enantiotropism. This is also in agreement with the density rule, because the low-temperature formII exhibits the higher density. Isothermal annealing of both modifications at different temperatures reveals a thermodynamic transition temperature of about 135 °C, which is in excellent agreement with that of 137.5 °C calculated from the melting temperatures and the heat of fusion of both forms. The high-temperature form can easily be prepared pure by solidification of the melt, which is in agreement with Ostwald's step rule, because formI crystallizes at a temperature where it is thermodynamically metastable. A qualitative energy/temperature diagram is presented.